Maimonides' Life of Learning - Finkel, Asher (Journal of Dharma, 1984)
Rabbi Moses ben Maimon, known as Maimonides, is perhaps the most famous and the greatest thinker of Medievel Judaism. l His fame has spread because of the influence of his writings which range in scope from medicine to philosophy and cover the entire field of rabbinic tradition. 2 The works were produced during his years of hardship and travel as well as during his stay in Egypt, where he served as the Sultan's physician and leader of the Jewish community. He was able to compose many great works written in Arabic and Hebrew, wide in scope and originality and of high quality. This prolific author, of amazing vigour and precision of intellectual, moral and religious force, was born in Cordova, Spain (1 135) and died in Cairo, Egypt (1204). His literarv work was remarkably comprehensive, touching upon the whole range of knowledge : from medicine to astronomy, Aristotelian logic and Islamic philosophy, ancient religions and magic, as well as Jewish law and social custom. He wrote epoch-making works